Сучасна білоруська національна історіографія у сприйнятті істориків з Білорусі - Івангородський, К. (Історіографічні дослідження в Україні, 2016)
У статті досліджено погляди білоруських істориків, присвячені аналізу сучасної білоруської національної історіографії. Основна увага звертається на негативні явища, властиві білоруській національній історичній науці на сучасному етапі. Окреслено перспективи розвитку білоруської історичної науки. In the article are investigated the Belarusian historians’ views devoted to the modern Belarusian national historiography analysis. The main attention is paid to the negative phenomena that is immanent to the Belarusian national historiography on modern stage. Prospects of the Belarusian historical science development are outlined.